Analisis Yuridis Peralihan Jaminan Fidusia Kepada Pihak Ketiga Tanpa Sepengetahuan Kreditur - Arya Dharma, Yafiz; Dintara Lubis, Syaddan (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
This study aims to analyze the legal consequences of the transfer of fiduciary collateral to a third party without the creditor's knowledge and the debtor's responsibility for such actions. The issue arises when a fiduciary creditor executes a process that violates existing procedures and regulations by seizing the collateral without selling or auctioning it. This execution is carried out due to time and cost considerations that are disproportionate to the expected results. The research employs a normative juridical approach, reviewing literature sources, including the Civil Code and Law No. 42 of 1999 concerning Fiduciary Guarantees. The study finds that fiduciary registration is a matter of publicity, meaning that all parties are deemed to be aware of the existence of fiduciary collateral through public access. Therefore, third parties transferring fiduciary objects must examine them carefully. The debtor's responsibility for transferring fiduciary collateral without the creditor's consent involves both civil and criminal consequences. This study highlights the importance of adhering to legal procedures to protect creditor rights and ensure debtor responsibility in fiduciary transactions.